Effects of a Pair Programming Educational Robot-Based Approach on Students’ Interdisciplinary Learning of Computational Thinking and Language Learning - Hsu, Ting-Chia; Chang, Ching; Wu, Long-Kai; Looi, Chee-Kit (Frontiers in Psychology, 2022)
Educational robotics (ER) activities are increasingly popular in integrating computational thinking (CT) with other cross-subject learning, such as foreign language (FL) learning. How to better help students acquire interdisciplinary learning, and examining its feasibility are both worth investigating. This study aimed to validate the effectiveness of pair programming (PP) on young learners’ CT skills and FL learning. Two Grade 6 classes, one with 16 students who were studying Chinese as a Second Language (CSL) as the control group (CG) and the other with 16 students who were studying English as a Foreign Language (EFL) as the experimental group (EG), participated in the activity. The CG students were paired up for the traditional ER-integrated pair programming activities (ER-integrated-PP), while the EG students worked on the ER-integrated-PP activities. Results indicated that both groups improved their CT and FL, but the CG’s progress in CT was more significant than that of the EG group. The EG group had better social skills of cooperation on CT and lower foreign language-learning anxiety than the CG group. Students’ learning behaviours in the EG demonstrated better involvement in discussion and negotiation loops, compared to the CG students who presented more behaviours on trial-and-error loops. Suggestions for using PP in ER-integrated interdisciplinary activities are given.